(untitled) (Sport - nauka i praksa, 2024)
Success in running depends on numerous factors, with two of the most important being stride length and stride frequency. The first goal of this study is to assess the differences in stride length and stride frequency between men and women at different running speeds. The second goal is to examine the correlation between the morphological characteristics of men and women with stride length and stride frequency. This study involved two groups of 37 recreational runners (22 men and 15 women). The participants ran on a treadmill, wearing two portable Prosense accelerometers on each ankle. The protocol included 10 minutes of running, consisting of 3 minutes of warming up at 8 km/h, one minute of running at 8, 10, 12, and 14 km/h (used for further analyses), and 3 minutes of running at 8 km/h. The main variables used were stride length and stride frequency. The results showed that women had a higher stride frequency than men at almost all running speeds (p < 0.05), but there was no difference in stride length between men and women. Additionally, men showed strong and statistically significant negative correlations between height and stride frequency (r >-0.59<-0.66), as well as low to moderate positive correlations between height and stride length (r >0.17<0.46). Among women, low to moderate negative correlations between height and stride frequency (r >-0.28<-0.43) were found, along with low to moderate positive correlations between height and stride length (r >0.34<0.52). The results of the study, as well as the modern technology used in this paper, would significantly improve the training process for recreational runners.